Kualitas Mikrobiologis Bakso Daging Sapi Diawetkan dengan Beberapa Level Konsentrasi Supernatan Bebas Sel Lactobacillus plantarum BAF514 pada Penyimpanan Suhu Refrigerator: Microbiological Quality of Preserved Beef Meatballs with Different Levels of Cell-Free Supernatants of Lactobacillus plantarum BAF514 at Refrigerated Temperature Storage - Afriani, Afriani; Elymaizar, Zulfa; Edy Wibowo, Sarwo Edy; Wulandari, Wulandari; Hariski, M. (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: Meatballs are a food that easily spoils if stored improperly. This spoilage is caused by microbial contamination. One way to reduce microbial contamination in meatballs is by using natural preservatives, such as cell-free supernatant from Lactobacillus plantarum. This cell-free supernatant contains antimicrobial metabolites that can effectively inhibit the growth of spoilage bacteria. Purpose: This study aims to determine the concentration of cell-free supernatant from Lactobacillus plantarum BAF514 as a biopreservative on the microbiological quality of beef meatballs stored at refrigerator temperature. Methods: A Completely Randomized Design (CRD) with 5 treatments and 4 replications was used in this study. The treatments consisted of: P1 = 100% cell-free supernatant, P2 = 90% cell-free supernatant + 10 ml sterile distilled water, P3 = 80% cell-free supernatant + 20 ml sterile distilled water, P4 = 70% cell-free supernatant + 30 ml sterile distilled water, and P5 = 60% cell-free supernatant + sterile distilled water. The variables observed were pH value, total microbes, Staphylococcus aureus, and Escherichia coli. Analysis of variance (ANOVA) was used in data analysis, Duncan's multiple range test was used if there was a significant effect. Results: The results showed that the use of several concentrations of 100% - 60% cell-free supernatant had a significant effect (P < 0.05) on pH and no significant effect (P > 0.05) on total microbes, Staphylococcus aureus, and Escherichia coli. The pH value of meatballs increased with the lower concentration of cell-free supernatant during storage. Conclusion: It was concluded that the use of cell-free supernatant concentration from Lactobacillus plantarum BAF514 on the microbiological quality of meatballs during refrigerator temperature storage did not increase the total microbes, Staphylococcus aureus and Escherichia coli but increased the pH value of the meatballs. The concentration of cell-free supernatant from Lactobacillus plantarum BAF514 up to 60% was still good for preserving beef meatballs stored at refrigerator temperature.